2005
DOI: 10.1093/ejo/cji028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth hormone on the craniofacial complex of transgenic mice

Abstract: Growth hormone (GH) secretion affects bone and cartilage physiology. This study investigated the effect of GH on the size of the craniofacial structures and their angular relationship. Three different models of mice with a genetically altered GH axis were used: GH excess (giant), dwarf GH antagonist (dwarf-Ant), and dwarf GH receptor knockout (dwarf-KO) mice. Each model was compared with the corresponding wild type (Wt). Five craniofacial distances were analysed: craniofacial length, upper face height, mandibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
0
33
0
3
Order By: Relevance
“…5,6 Growth hormone (GH), a peptide hormone produced in the anterior pituitary, plays a major role in regulating growth and development of the maxillofacial complex. 7 GH binds growth hormone receptors (GHRs) located on the cell surface in order to activate the intracellular signaling pathways involved in these processes. 8 GH plays an important role in the growth of cartilage, and GHRs are especially present in the mandibular condyle, 9,10 which plays a significant role in the growth and development of craniofacial morphology by regulating the angle and size of the morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Growth hormone (GH), a peptide hormone produced in the anterior pituitary, plays a major role in regulating growth and development of the maxillofacial complex. 7 GH binds growth hormone receptors (GHRs) located on the cell surface in order to activate the intracellular signaling pathways involved in these processes. 8 GH plays an important role in the growth of cartilage, and GHRs are especially present in the mandibular condyle, 9,10 which plays a significant role in the growth and development of craniofacial morphology by regulating the angle and size of the morphology.…”
Section: Introductionmentioning
confidence: 99%
“…8 GH plays an important role in the growth of cartilage, and GHRs are especially present in the mandibular condyle, 9,10 which plays a significant role in the growth and development of craniofacial morphology by regulating the angle and size of the morphology. 7 Dysfunctional mutations in the GHR gene cause Laron syndrome (GH insensitivity syndrome), which is associated with characteristic craniofacial morphology and short stature. 11 Interestingly, patients with GHR defi-ciency exhibit craniofacial morphology characterized by poor vertical growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth hormone (GH) is a craniofacial morphological determinant; it plays a major role in the growth and development of the craniofacial complex by directly and indirectly modulating the size and the angular relationships of the craniofacial structures (Ramirez-Yanez et al, 2005). Children with deficient or excess GH have been reported to develop unique craniofacial configurations (Pirinen et al, 1994).…”
Section: Mandibular Morphology and The Growth Hormone Receptor Genementioning
confidence: 99%
“…Analysis of the Ghr knockout mouse has revealed that the GH→GHR→insulin-like growth factor 1 system is important in postnatal growth and that GHR plays a role in maintaining proportional skeletal growth (Sjogren et al, 2000). In Ghr knockout mice, the height of the mandibular ramus is significantly reduced (Ramirez-Yanez et al, 2005), and disproportionate skeletal growth is reflected by decreased femur:crown-rump and femur:tibia ratios (Sjogren et al, 2000). There are diverse mutations and polymorphisms in the GHR gene in humans.…”
Section: Mandibular Morphology and The Growth Hormone Receptor Genementioning
confidence: 99%